Causal Association Between Genetically Predicted Ankle Spacing Width and Risk of Age-Related Bone Mineral Density - Xian-Pei Xiao; Yong-Jun Dai; Hong-Xu Li; Jun-Jie Mao; Bi-Yuan Qin (Scientific Reports)
Abstract While observational studies suggest associations between ankle spacing width (ASW, defined as the horizontal distance between the medial malleoli under weight-bearing conditions) and osteoporosis (OP), fractures, and falls, causal evidence remains limited. This gap hinders the translation of ASW measurements into clinical risk stratification tools. This study aimed to investigate the causal relationships between ASW indicators and site-/age-specific bone mineral density (BMD), bone fracture and fall risks. Genetic exposure data for ASW indicators were retrieved from the MRC-IEU datasets, and the outcome data were all derived from the Genetic Factors for Osteoporosis Consortium (GEFO). Genome-wide associations of single nucleotides polymorphisms (SNPs) were served as instrumental variables (IVs) to infer causal effects using two-sample mendelian randomization (TSMR) and multivariable mendelian randomization (MVMR) analyses. The results of sites-specific TSMR analysis revealed that per unit increase in ASW (including left and right) were causally associated with lower estimated from quantitative heel ultrasounds BMD (eBMD, reflecting calcaneal bone density) and total-body BMD (TB-BMD, assessed via DEXA scans), with pronounced effects in individuals aged over 60 years. Age-stratified analyses revealed no significant associations between ASW and TB-BMD in younger age groups (age ≤ 15, 15 < age ≤ 30, 30 < age ≤ 45, 45 < age ≤ 60) or site-specific fractures/falls. MVMR adjustment for BMI, smoking, and alcohol consumption confirmed persistent causal associations between ASW and reduced eBMD and TB-BMD, particularly for TB-BMD in individuals aged over 60 years. Our study provides evidence that genetically predicted ASW is associated with reduced eBMD and TB-BMD, and a causal association between ASW and TB-BMD (aged over 60), suggesting ASW as a potential auxiliary biomarker for monitoring age-dependent bone loss.